A rare clinical case of the isolated primary frontal bone osteoma - Pohranychna, Kh. (Experimental Oncology, 2016)
Aim: To study a rare clinical case of isolated primary osteoma localized in the frontal bone, provide its detailed clinical and pathomorphological analysis, and evaluate statistical indicators of occurrence frequency and localization of facial skeleton osteomas during 2006–2015. Materials and Methods: The retrospective case records analysis of patients undergoing treatment in the maxillofacial department of Lviv Regional Clinical Hospital and suffering from facial skeleton osteomas was conducted. The clinical examination was carried out in accordance with the inspection protocol required for the examination of patients diagnosed with tumors and tumorlike neoplasms in a particular clinical case. Frontal and lateral views were used in the course of Xray imaging. Histological studies included macroscopy and microscopy. Results: According to the retrospective case record analysis made over the last 10 years 346 cases of facial bone osteoma were revealed and proved histologically comprising 3.7% of all benign osteogeneous maxillofacial tumors. For the first time in 10 years osteoma localized in the frontal bone had been revealed and thoroughly studied. Macroscopically — a semispherical and immovable neoformation 7 cm in diameter of hard consistency, splaying out at 4 cm and being adherent with the frontal bone. Roentgenologically — homogeneous intense shadowing of a round form with relatively distinct outlines complying with clinical sizes. According to the histological data, the tumor consists mostly of the solid osseous tissue and the spongy osseous tissue with the evident thickened trabeculas of the bone located in different directions. Conclusion: The analysis of historical data demonstrated extremely rare localization of primary osteoma of the frontal bone, and indicated the uniqueness of the case and significant clinical importance of its detailed study.